Branding in SMEs: Practices, Processes, and Stakeholder Roles at Abi Goes Tallinn - Partanen, Veikka (My University, 2025)
This thesis explores the role of branding in small and medium-sized enterprises (SMEs) through a qualitative case study of a Finnish event brand Abi Goes Tallinn (AGT). Branding is often discussed in the context of large corporations and their considerable marketing budgets, but less attention is given to how SMEs optimize their limited resources to develop and maintain their brands. This study focuses on SME branding practices and processes, and how employees and customers contribute to its communication and perception. The research was guided by Kevin Lane Keller’s Customer-Based Brand Equity model and the research questions derived from it. The data was collected through six semi-structured interviews: three with AGT employees and three with customers. After collection, the data was thematically coded with the help of a codebook, identifying patterns related to brand identity, stakeholder roles (internal and external), and overall brand perception. The findings indicate that branding in SMEs is not an isolated marketing function, but an integral and continuous process embedded in day-to-day operations, company culture and customer experiences. AGT’s brand is shaped by strong internal alignment, cost-effective marketing tools like social media, and active engagement from both employees and customers. Customers play a vital role in amplifying the brand through word-of-mouth and user-generated social media content, reinforcing emotional connections and brand resonance. This study concludes that branding has a critical role in SME operations. It is argued that in SME branding, success does not necessarily arise from scale, but rather from consistency, values and emotional connection. When developing an SME’s brand, balancing a combination of strategic planning and organic development allows the brand to evolve naturally and remain aligned with its fundamental values. The study also includes limitations: the small sample size must be acknowledged when evaluating the applicability of the results in a broader context.

Tässä pro gradu -tutkielmassa tutkitaan brändäyksen roolia pienissä ja keskisuurissa yrityksissä (pk-yrityksissä). Tutkimus tehdään laadullisena case -tutkimuksena, joka keskittyy suomalaiseen Abi Goes Tallinn (AGT) brändiin. Brändäyksestä keskusteltaessa keskitytään yleensä suuriin yrityksiin ja niiden mittaviin markkinointibudjetteihin, mutta huomattavasti vähemmän huomiota keskitetään pk-yritysten tapaan optimoida rajalliset resurssinsa ja kehittää brändejään. Tämä tutkimus keskittyy pk-yritysten brändäyskäytäntöihin ja prosesseihin, ja siihen miten työntekijät ja asiakkaat ovat osallisena brändin viestinnässä. Tutkimusta ohjasi Kevin Lane Kellerin asiakaslähtöisen brändipääoman malli ja siitä johdetut tutkimuskysymykset. Tutkimusaineisto kerättiin kuudella puolistrukturoidulla haastattelulla: kolme AGT:n työntekijää ja kolme asiakasta. Aineisto koodattiin temaattisesti koodikirjan avulla, jotta siitä voitiin tunnistaa brändi-identiteettiin, sidosryhmien rooleihin ja yleiseen brändikäsitykseen liittyviä havaintoja. Tulokset osoittavat, että pk-yritysten brändäys ei ole pelkästään erillinen markkinointitoiminto, vaan keskeinen ja jatkuva prosessi, joka on juurtunut syvälle päivittäisiin toimintoihin, yrityskulttuuriin ja asiakaskokemuksiin. AGT:n brändiä muovaa vahva sisäinen asennoituminen, kustannustehokkaat markkinointikanavat kuten sosiaalinen media, ja sekä työntekijöiden että asiakkaiden aktiivinen sitoutuminen brändiin. Asiakkailla on elintärkeä rooli brändin vahvistamisessa ns. ”puskaradioviestinnän” ja käyttäjien luoman sosiaalisen median sisällön keinoin. Johtopäätöksenä on, että brändäyksellä on tärkeä rooli pk-yrityksen toiminnoissa. Tutkimus esittää, että pk-yritysten brändäyksessä menestys ei tule niinkään toiminnan suuresta skaalasta, vaan yhtenäisyydestä, arvoista ja tunneyhteydestä. Strategisen suunnittelun ja orgaanisen kehityksen tasapainoinen yhdistelmä mahdollistaa brändin luonnollisen kehittymisen, samalla pysyen arvoilleen uskollisena. Tutkimuksessa on myös rajoituksia: rajallinen otoskoko täytyy ottaa huomioon tulosten laajempaa soveltuvuutta arvioitaessa.
Keywords: branding, brand, SME, customer-based brand equity, brändäys, brändi, pk-yritys, asiakaslähtöinen brändipääoma